TB & Tobacco (Faculty of Medicine Universitas Indonesia, 2003)
One third of the world population is infected with tuberculosis, and over 8 millions people were developing each year. On the other hand tobacco is responsible for 3 millions death in the world. For Indonesia, our country has the third biggest TB cases in the world. Whereas Indonesia is ranked as having the fourth largest number of smokers in the world. A relationship between smoking and TB has been suspected for a long time, even though the epidemiological evidence has not been convincing so far, as well as the pathophysiology and the biomolecullar changes. At present time there are more and more epidemiological data to suggest relationship between TB and tobacco. Further research should be done to get more indepth relationship as well as avoiding the confounder factor. To be able to perform TB control as well as tobacco control successfully there should be emphasize on synergistic public health approaches. Tuberculosis âwhich Indonesia got 3rd rank in the world- as well as smoking problem âwhich Indonesia got 4th rank in the world- are two important public health problem for the country. If there are relationship between tobacco and tuberculosis, health problem faced by Indonesian even become bigger. Knowledge about tuberculosis as well as tobacco among Indonesian population is very essential to improve the public health situation. Tuberculosis control programme as well as smoking control programme are essential tools for the well being of Indonesian people. (Med J Indones 2003; 12: 48-52) Keywords: tobacco, tuberculosis, epidemiological data